A critical review on the fabrication techniques that can enable higher throughput in dielectrophoresis devices. Issue 1 (27th September 2021) - Martinez‐Duarte, Rodrigo
Abstract: The sorting of targeted cells in a sample is a cornerstone of healthcare diagnostics and therapeutics. This work focuses on the use of dielectrophoresis for the selective sorting of targeted bioparticles in a sample and how the lack of throughput has been one important practical challenge to its widespread practical implementation. Increasing the cross‐sectional area of a channel can lead to higher flow rates and thus the capability to process a larger sample volume per unit of time. However, the required electric field gradient that is generated by polarized electrodes drastically decreases as one moves away from the electrodes. Hence, the scaling up of the channel cross section must be done asymmetrically. One desires a channel aspect ratio AR = height/width that is much smaller or much larger than 1. Since reducing footprint of the DEP device is important to ensure affordability, the use of channels with AR ≫ 1 is desired. This creates the challenge to fabricate electrodes on the sidewalls of multiple channels with AR ≫ 1, or a channel embedding an array of electrodes with a gap in between them with AR ≫ 1. This critical review first details the motivation for using three‐dimensional (3D) DEP devices to improve throughput and then describes selected techniques that have been used to fabricate them. Techniques include electrodeposition, deep etching, thick‐film photolithography, and co‐fabrication. Electrode materials addressed include metals, silicon, carbon, PDMS‐based composites as well as conductive polymers and fluids.